2018
DOI: 10.1002/cam4.1588
|View full text |Cite
|
Sign up to set email alerts
|

Highlights on molecular targets for radiosensitization of breast cancer cells: Current research status and prospects

Abstract: In the past, searching for effective radiotherapy sensitization molecular targets and improving the radiation sensitivity of malignant tumors was the hot topic for the oncologists, but with little achievements. We will summarize the research results about breast cancer irradiation sensitization molecular targets over the past two decades; we mainly focus on the following aspects: DNA damage repair and radiation sensitization, cell cycle regulation and radiation sensitization, cell autophagy regulation and radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…There is intense interest in the discovery of radiosensitizing agents for breast cancer [18] and this study highlights the potential of translation-initiation as another avenue for target discovery.…”
Section: Discussionmentioning
confidence: 98%
“…There is intense interest in the discovery of radiosensitizing agents for breast cancer [18] and this study highlights the potential of translation-initiation as another avenue for target discovery.…”
Section: Discussionmentioning
confidence: 98%
“…A great challenge is identifying individuals who have a high risk of recurrence. Genetic testing provides valuable prognostic information for early-stage patients with breast cancer in order to obtain possible prognostic information as part of their treatment regimens [ 9 ]. Gene expression profiles and whole genome sequencing are increasingly being incorporated into the treatment planning process for breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…H19, an imprinted lncRNA, is one of the first identified lncRNAs 16. Accumulating evidence reveals that the dysregulated H19 acts as the tumorigenic and anti-tumorigenic roles in many tumors, such as bladder cancer,17 breast cancer 18. Huang et al have reported that H19 are associated with cell invasion and metastasis in EC 19.…”
Section: Introductionmentioning
confidence: 99%